Characterisation of Staphylococcal and Candida Populations from Healthy and Diseased Oral and Subgingival Sites Reveals a High Prevalence and Diversity of the Arginine Catabolic Mobile Element ACME in Staphylococcus epidermidis - O'Connor, Aoife (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2018)
The oral cavity harbours a diverse microbiological population, that exists mainly as plaque biofilm, the accumulation of which is associated with oral diseases such as periodontal disease and peri-implantitis. Traditionally, staphylococci were considered transient members of the oral flora, and not thought to contribute to plaque-associated diseases. In contrast, Candida species, particularly Candida albicans, are well-recognised oral commensals and opportunistic pathogens. Detailed investigations of oral staphylococcal and Candida populations in healthy individuals with and without dental implants and in patients with periodontal disease are currently lacking. The aim of this study was to determine the prevalence and abundance of staphylococcal and Candida species in periodontal pockets, subgingival sites and oral rinses from patients with periodontal disease (n=20), healthy patients with dental implants (n=31) and orally healthy participants without implants (n=64). Participants were subjected to oral rinse, nasal, periodontal pocket and subgingival site sampling. Staphylococci were recovered on selective agar media and definitively identified by Matrix Assisted Laser Desorption Ionization Time-of-Flight analysis. Candida species were recovered on CHROMagar Candida? medium (CHROMagar, France) and definitively identified by polymerase chain reaction (PCR) using species-specific primers. Staphylococci were prevalent in all three participant groups and Staphylococcus epidermidis predominated in all oral sites investigated. This species was most prevalent in oral rinses (18/20, 90%), periodontal pockets (6/20, 30%) and subgingival sites (4/20, 20%) of patients with periodontal disease, but was also highly prevalent in healthy patients with implants [oral rinses (25/31, 80.6%) and subgingival sites (5/31, 16.1%)] and in orally healthy participants [oral rinses (43/64, 67.2%) and subgingival sites (5/64, 7.8%)]. The average cell density of S. epidermidis was also significantly higher in oral rinses from patients with periodontal disease [82.4 ? 218.9 colony forming units (CFU)/ml] compared to orally healthy participants [20.4 ? 14.8 CFU/ml] (p = 0.0153). In contrast, Staphylococcus aureus was much less prevalent [patients with periodontal disease: oral rinses (5/20, 25%), periodontal pockets (0/20, 0%) and subgingival sites (0/20, 0%); healthy patients with implants: oral rinses (15/31, 48.4%), subgingival sites (4/31, 12.9%); orally healthy participants: oral rinses (19/64, 29.7%), subgingival sites (5/64, 7.8%)]. Candida albicans predominated in all participant groups [patients with periodontal disease: oral rinses (11/20, 55%), periodontal pockets (4/20, 20%) and subgingival sites (2/20, 10%); healthy patients with implants: oral rinses (14/31, 45.2%) and subgingival sites (7/31, 22.6%); orally healthy participants: oral rinses (17/64, 26.6%) and subgingival sites (3/64, 4.7%)]. The average C. albicans cell density was also significantly higher (p = <0.05) in oral rinses of patients with periodontal disease (215.2 ? 487.8 CFU/ml) than in the other participant groups (34.7 ? 70.6 CFU/ml and 7.8 ? 25.9 CFU/ml). In total 227 S. epidermidis and 78 S. aureus oral-nasal isolates were screened using the S. aureus Genotyping Kit 2.0 microarray system (Alere, Germany) and 24 C. albicans isolates underwent ABC genotyping and multilocus sequence typing (MLST) using the current consensus MLST scheme for C. albicans (www.pubmlst.org/calbicans) to identify genomic markers or clonal lineages that might be associated with a participant group, anatomical sites or oral disease state(s). A diverse population of C. albicans isolates was identified among the three groups of participants by MLST. No clonal lineages were particularly associated with oral health status or anatomical site. Diverse populations of S. aureus and S. epidermidis were also detected in all three participant groups by microarray profiling. Genes encoding resistance to antimicrobial agents including macrolides, tetracycline, and methicillin were more prevalent in S. epidermidis, whereas genes encoding virulence factors were typically more prevalent in S. aureus. Interestingly, microarray profiling revealed that the arc genes carried by the arginine catabolic mobile element (ACME) were highly prevalent in oral S. epidermidis. The prevalence of each of three previously described ACME types (I: arc and opp3 genes, II: arc genes only, and III: opp3 genes only) was investigated in 143 S. epidermidis isolates by multiplex PCR using ACME-arc- and ACME-opp3-specific primers. A total of 85/143 (59.4%) isolates harboured ACME, of which 60/85 (70.6%) harboured ACME II, 16/85 (18.8%) harboured ACME I and 9/85 (10.6%) harboured ACME III. ACME was significantly (p = 0.016) more prevalent among isolates from periodontal pockets (7/9, 83%) compared to subgingival sites of healthy participants (3/5, 60%). The genomic diversity of 25 ACMEs from S. epidermidis isolates selected as representative of participant groups and oral sites [type I (n=2), type II (n=20) and type III (n=3)] was investigated by whole genome sequencing (WGS). This was the first detailed investigation of the structural organisation of ACME type III to date. Surprisingly, all three ACME III-positive isolates belonged to the extremely rare S. epidermidis sequence type (ST) ST329, suggesting that this ST may represent an ancestral strain of historic ACME rearrangements that retains ACME III as a remnant. The ACMEs characterised were frequently components of composite genetic elements, often co-located with staphylococcal cassette chromosome (SCC)-associated genes. Based on the size of the elements and presence or absence of SCC-associated genes, highly diverse composite elements were identified in 16/25 isolates in association with ACME types I-III. Typically copA is located at the 3' end of ACME, and the ars operon located downstream of ACME, however, these were internalised within ACME composites containing ACME I (n=2) and III (n=3) and directly into ACME II (n=2) highlighting the genomic plasticity of these elements. The ACME-arc operon encodes an arginine deaminase pathway thought to enable staphylococcal persistence in nutrient and oxygen poor environments by metabolism of L-arginine for energy and pH regulation. Based on the high prevalence of ACME-arc and the low prevalence of ACME III lacking ACME-arc in periodontal pockets and subgingival sites, it is likely that this operon facilitates the adaptation of S. epidermidis to the semi-anaerobic environment of these sites. The present study revealed a significant enrichment of S. epidermidis harbouring a diverse range of ACMEs in subgingival sites and periodontal pockets of patients with periodontal disease, particularly ACME types encoding the arc-genes, suggesting that these genes confer a survival advantage on S. epidermidis in these diseased semi-anaerobic sites.
APPROVED
Keywords: Periodontal Disease; Staphylococcus epidermidis; Staphylococcus aureus; Candida albicans; Oral Cavity; Periodontal pocket; Arginine catabolic mobile element (ACME); Subgingival site